Household Inflation Expectations: Information Gathering, Inattentive or 'Stubborn'? - Joshy Easaw; Roberto Golinelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
The purpose of this paper is to investigate the microfoundations of how non-experts' (or general public) form inflation expectations. Using a unique dataset we investigate the range of near rational inflation expectations. An important contribution to understanding how non-experts form their expectations is 'sticky information expectations', specifically the epidemiological model. Our analysis uses an extended version of the epidemiological model. We find that the general public are best depicted as those who are either information gathers or inattentive. In addition, the inattentive general public can be either forward-looking or 'stubborn', that is persistent.
Keywords: D84; E31; 330